Redox priming could be an appropriate technique to minimize drought-induced adversities in quinoa - Iqbal, Hassan; Yaning, Chen (Frontiers in Plant Science, 2024)
The exogenous use of the redox compound (H2O2) plays a significant role in abiotic stress tolerance. The present study investigated various H2O2 application methods (seed priming, foliar spray, and surface irrigation) with varying concentration levels (0 mM, 5 mM, 10 mM, 15 mM, 40 mM, 80 mM, and 160 mM) to evaluate the efficiency of supplying exogenous H2O2 to quinoa under water-deficit conditions. Drought stress reduced quinoa growth and yield by perturbing morphological traits, leading to the overproduction of reactive oxygen species and increased electrolyte leakage. Although all studied modes of H2O2 application improved quinoa performance, surface irrigation was found to be sensitive, causing oxidative damage in the present study. Seed priming showed a prominent increase in plant height due to profound emergence indexes compared to other modes under drought conditions. Strikingly, seed priming followed by foliar spray improved drought tolerance in quinoa and showed higher grain yield compared to surface irrigations. This increase in the yield performance of quinoa was attributed to improvements in total chlorophyll (37%), leaf relative water content (RWC; 20%), superoxide dismutase (SOD; 35%), peroxidase (97%), polyphenol oxidase (60%), and phenylalanine ammonia-lyase (58%) activities, and the accumulation of glycine betaine (96%), total soluble protein (TSP; 17%), proline contents (35%), and the highest reduction in leaf malondialdehyde contents (MDA; 36%) under drought stress. PCA analysis indicated that physio-biochemical traits (proline, SOD, TSP, total chlorophyll, MSI, and RWC) were strongly positively correlated with grain yield, and their contribution was much higher in redox priming than other application methods. In conclusion, exogenous H2O2 application, preferably redox priming, could be chosen to decrease drought-induced performance and yield losses in quinoa.